2015
DOI: 10.31899/pgy9.1085
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of son preference and resulting demographic and health outcomes in Pakistan

Abstract: The Population Council confronts critical health and development issues-from stopping the spread of HIV to improving reproductive health and ensuring that young people lead full and productive lives. Through biomedical, social science, and public health research in 50 countries, we work with our partners to deliver solutions that lead to more effective policies, programs, and technologies that improve lives around the world. Established in 1952 and headquartered in New York, the Council is a nongovernmental, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Heterogeneous Treatment Effects.-We report heterogeneous treatment effects, estimated separately for each gender of the index child, since in South Asia son preference leads to investments and outcomes often favoring sons (Sathar et al 2015;Miller 1981; Bhalotra, Chakravarty, and Gulesci 2020) and mothers of sons (Milazzo 2018, Bhalotra et al 2018. Additionally, males are biologically more sensitive to stress in utero (Trivers and Willard 1973), and male and female children respond differently to early life shocks (Autor et al 2016, Bhalotra andVenkataramani 2011).…”
Section: Econometric Specificationmentioning
confidence: 99%
“…Heterogeneous Treatment Effects.-We report heterogeneous treatment effects, estimated separately for each gender of the index child, since in South Asia son preference leads to investments and outcomes often favoring sons (Sathar et al 2015;Miller 1981; Bhalotra, Chakravarty, and Gulesci 2020) and mothers of sons (Milazzo 2018, Bhalotra et al 2018. Additionally, males are biologically more sensitive to stress in utero (Trivers and Willard 1973), and male and female children respond differently to early life shocks (Autor et al 2016, Bhalotra andVenkataramani 2011).…”
Section: Econometric Specificationmentioning
confidence: 99%
“…Thus, the elevated sex ratio at birth for the 2002–06 period is unlikely due to data quality issues (as suggested by other studies; see Sathar et al. ).…”
Section: Resultsmentioning
confidence: 76%
“…Likewise, interviews with medical professionals in a large Pakistani urban center found that sex‐selective abortions are not perceived to be common practice (Sathar et al. ). Repeatedly doctors in this study reported that ultrasound could not reliably identify the sex of a fetus until the twelfth week of pregnancy and that abortions at that duration were not recommended or common practice.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Accordingly, most obstetricians in our study would not offer NIPT for sex determination, but a significant minority would. The latter finding may be because the preference for male children is deeply embedded in Pakistani culture, yet doctors are not concerned about the possibility of sex selection leading to an imbalance of sex ratio to male sex, as observed in countries like China and India, because abortion on social grounds (including fetal sex) is illegal in Pakistan, religiously impermissible (unless the mother's life is threatened) and culturally disapproved . Nevertheless, our finding raises concerns about the potential use of NIPT for sex determination and further highlights the importance of national policy to regulate the implementation of NIPT for medical purposes only …”
Section: Discussionmentioning
confidence: 89%